Assessment of three wind reanalyses in the North Atlantic Ocean. Issue 1 (2nd January 2017) - Campos, Ricardo Martins; Guedes Soares, Carlos
ABSTRACT: This paper evaluates three surface wind reanalyses in the North Atlantic Ocean: Climate Forecast System Reanalysis (CFSR/NOAA), ERA-Interim/ECMWF and the Hindcast of Dynamic Processes of the Ocean and Coastal Areas of Europe (HIPOCAS) based on the regional atmospheric model (REMO). The assessment is performed using satellite data from the GlobWave Project. The first part of this study compares the reanalyses in spatial and temporal domains. Furthermore, the analysis is also divided into overall conditions and extreme events. The second part evaluates each reanalysis independently using satellite data. In order to compare and evaluate the three datasets, coincident periods and grid domain were determined, which corresponds to the interval between 1979 and 2001, latitudes between 15° and 72° North and longitudes between 66° West and 7° East. The comparison results show that under calm winds the agreement among reanalyses is good. However, an increasing difference is found under extreme conditions. For extreme events, HIPOCAS (REMO) has the strongest winds, followed by CFSR and ERA-Interim. The assessment using measurements indicates underestimation of winds at mid–high latitudes above 45° North and overestimation at low latitudes. The monthly analysis suggests a strong seasonal cycle with overestimation of all reanalyses in the summer and underestimation in the winter. The lowest errors and best performance was obtained by CFSR, followed by HIPOCAS (REMO) at mid–high latitudes and ERA-Interim at low latitudes. A significant underestimation of ERA-Interim for the peak of the storms was found, which can be associated with its coarse time and space resolution.